The controlling concept cornerstone of performance management - Horváth, Péter, 1937- (World Scientific, 2020)
"The Controlling Concept: Cornerstone of Performance Management is a guide to controlling, and how to adopt controlling effectively in business practice. This book describes, by means of the "House of Controlling", how you can effectively implement controlling in your business practice. For instance, it clarifies the following questions: What is the heart of the controlling concept? Which subject areas are covered by an effective controlling system? What does state-of-the-art controlling look like? By what measures can the success of controlling be determined? How can the effectiveness and efficiency of controlling be improved? How is controlling continuing to develop? Chapters are supplemented by organisational checklists and business practice examples, drawn from Horváth & Partners' many years of experience developing and implementing controlling concepts at home and abroad"--Publisher's website.